2013
DOI: 10.1108/20400701311303159
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of utilization of antenatal care services in developing countries

Abstract: PurposeThe purpose of this paper is to estimate the key socio‐economic and demographic factors influencing the utilization of antenatal care services in Ghana.Design/methodology/approachThe paper utilizes the most recent Ghana Demographic and Health Survey (GDHS V) data. The dependent variable is the intensity of utilization (number) of antenatal care visits. Hence, the negative binomial regression is employed to investigate the socio‐economic and demographic correlates of the intensity of antenatal care utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 29 publications
28
48
0
Order By: Relevance
“…However, we found that they were more likely to have attended ANC at least four times if they had enrolled in the health insurance scheme. Consistent with those of earlier studies [4,36,42–49], the findings of the current study demonstrated the importance of health insurance in seeking and receiving healthcare. Implementation of the Ghanaian government policy for free medical care for pregnant women under the NHIS could have been a factor in increasing ANC attendance.…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that they were more likely to have attended ANC at least four times if they had enrolled in the health insurance scheme. Consistent with those of earlier studies [4,36,42–49], the findings of the current study demonstrated the importance of health insurance in seeking and receiving healthcare. Implementation of the Ghanaian government policy for free medical care for pregnant women under the NHIS could have been a factor in increasing ANC attendance.…”
Section: Discussionsupporting
confidence: 92%
“…This result of relatively easy access to ANC by the rural women is encouraging. A high level of accessibility to ANC has a positive influence on the level of utilisation, as found by previous studies in other African countries such as Ghana (Addai, 2000;Buor, 2004;Nketiah-Amponsah et al, 2013;Asundep et al, 2013), Ethiopia (Mekonnen and Mekonnen, 2003;Girma et al, 2011;Tsegay et al, 2013) and Nigeria (Dahiru and Oche, 2015). Increased utilisation results in positive health outcomes such as reduced maternal and infant morbidity and mortality resulting from of pregnancy and birth complications.…”
Section: Discussionsupporting
confidence: 52%
“…The WHO estimated Ghana's maternal mortality ratio at 376 per 100,000 live births in 2005, 325 per 100,000 in 2010, and 319 per 100,000 in 2015 (World Health Organization, 2015). Inadequate access, low quality and underutilisation of modern ANC services are key reasons for poor maternal and infant health outcomes in Ghana and other Sub-Saharan African countries (Nketiah-Amponsah et al, 2013;Escribano-Ferrer et al, 2016;Emelumadu et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Communities were not randomly assigned to intervention or comparison areas. There were differences between the intervention and comparison areas at baseline in terms of ethnicity, which studies have shown to be associated with uptake of ANC services (Abor et al 2011;Nketiah-Amponsah, Senadza, and Arthur 2013;Pell et al 2013). Additionally, this study did not follow a cohort of mothers, but rather selected separate pre-post samples at baseline and follow-up in both programme areas.…”
Section: Comparison Areamentioning
confidence: 99%